Devolution and empowerment LGC 1991 and Local Autonomy in the Philippines - Tapales, Proserpina D. (Philippine Journal of Public Administration, 1992)
The effort to attain genuine local autonomy has been exerted since the framing of the Malolos Constitution. Such effort recently bore fruit with the enactment of Republic Act 7160 otherwise known as the Local Government Code of 1991. This code prescribes a decentralization system whereby local government units shall be given more powers, authority, responsibility, and resources to enable them to function with limited national government support. The system is made operational through the devolution of services, strengthening of people's participation in local development, provision of increased shares in nationally imposed taxes, and strengthening of local officials and councils.